International law in world politics : an introduction - Scott, Shirley V. (Boulder, Colo : Lynne Rienner Publishers, 2010)
The Copenhagen Climate Change Conference. Iran's plans to build nuclear weapons. Ongoing armed conflict in Congo, Iraq, and Afghanistan. Debates about the responsibility to protect. In each of these headline events, the complex relationship of international law and world politics comes into play. The second edition of International Law in World Politics--thoroughly updated and now including a full chapter on the use of force--introduces the concepts, the rules, and the functioning of international law in a way that is accessible to students of political science. Shirley Scott covers such core topics as the nature of legal argument, the negotiation and implementation of multilateral treaties, and the place of both intergovernmental organizations and nonstate actors in the international legal system. Equally important, she connects the content of laws to current issues and problems, using case studies to bring the subject to life. The result is a rare text that effectively explains the role that international law plays in the changing arena of world politics. "Writing an easily accessible but still comprehensive text on the role of international law in current world politics is not easy, yet it is exactly what Shirley Scott has accomplished with this excellent introductory book."--Hanne Hagtvedt Vik, Journal of Peace Research.
International law and world politics entwined -- States in international law -- Intergovernmental organizations in international law -- Nonstate actors in international law -- The logical structure of international law -- International law and the use of force -- Legal argument as political maneuvering -- Reading a multilateral treaty -- The evolution of a multilateral treaty regime -- International law and arms control -- International human rights law -- International humanitarian law -- International law and the environment -- The future role of international law in world politics.
Includes bibliographical references and index.
Keywords: International law